Propose Corporate Performance Management System In PT CDE (The Indonesian Journal of Business Administration, 2021)
PT CDE, is one of the original aerospace companies in Asia with core competencies in aircraft design and development, aircraft structure manufacturing, aircraft production, and aircraft services for civil and military light and medium aircraft. However, in recent years CDE has had a fluctuating performance, company face several challenges to develop performance management system to maintain corporate performance to achieve targets and further to achieve the vision and corporate mission.The performance management system proposed using the Balanced Scorecard (BSC) framework by Kaplan and Norton (1992), Performance Prism (PP) Neely (2002) and Wibisono's Integrated Performance Management System (IPMS) (2003) from the three frameworks will be proposed. the most suitable framework to be proposed will be used by CDE. It is hoped that implementing this performance management system can help solve the problems faced by CDE. Each perspective has measurable indicators to measure its achievement. Knowing the achievement of each indicator is expected to become a monitoring system which is the starting point for further analysis and can be used as input for decision making for management.Keywords: performance management system; Balanced Scorecard (BSC); Performance Prism (PP); Integrated Performance Management System (IPMS)